RETHINKING BOARD ROLES PERFORMANCE: TOWARDS INTEGRATIVE MODEL - Babić, Verica; Nikolić, Jelena; Erić, Jelena (Economic Annals, 2011)
This research focuses on the board role evolution analysis which took place simultaneously with the development of different corporate governance theories and perspectives. The purpose of this paper is to provide understanding of key factors that make a board effective in the performance of its role. We argue that analysis of board role performance should incorporate both structural and process variables. This paper’s contribution is the development of an integrative model that aims to establish the relationship between the board structure and processes on the one hand, and board role performance on the other.